2017 National Magnet Nurses of the Year®. (February 2018) - Graystone, Rebecca
Abstract : The Magnet Recognition Program® recognizes healthcare organizations for quality patient care, nursing excellence, and innovations in professional nursing practice. Consumers rely on the Magnet designation as the ultimate credential for high-quality nursing. The ANCC National Magnet Nurse of the Year® awards were created in 2010 to recognize the outstanding contributions of clinical nurses for innovation, consultation, leadership, and professional risk taking.